The Impact of GeoGebra on Senior Secondary Students’ Performance in Algebra - Adesina, Olugbenga Alani; Sosanwo, Temitope Abosede (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study investigates the effectiveness of GeoGebra as a dynamic mathematics software tool in improving the performance of senior secondary students in Algebra. A group of 100 students were selected from a senior secondary school and divided into two groups of 50 each. A quasi-experimental design was utilised, involving a control group and an experimental group taught using traditional methods and GeoGebra, respectively. Pre-tests and post-tests were administered to assess improvement in students' understanding and performance in Algebra. The result was analysed, and the findings indicate that students using GeoGebra outperformed their peers in the control group, suggesting that the integration of technology in mathematics education can enhance student learning outcomes.